Titles and Abstracts in Academic Discourse - Jariah Mohd. Jan (Journal of Modern Languages)
This study examines the language of titles and abstracts in writing theses. The focus of this paper is two-fold; first, to investigate the rhetorical structure or styles of writing abstracts, and second, to determine features of a good title. The results of the paper indicate that writers of theses should inculcate the skills of writing abstracts. Employing the suggested techniques or strategies would be a step in ensuring good production of abstracts. The analysis of the papers also shows that the generality or specificity of a title correlates with the number of lexical units in the title. That is, as the number of the lexical units increase the title becomes more specific.